852. KEWA ACIDA: Kewaceae Plant in Peril 39. (December 2016) - Christenhusz, Maarten J. M.; Clubbe, Colin; Hilgenhof, Rebecca; Fay, Michael F.
Summary: Recent studies showed that a group of Hypertelis species was neither related to the type of that genus or to other members of Molluginaceae. As a result, these species were segregated as a new genus in its own family, Kewaceae. The St Helenan endemic Kewa acida (Hook.) Christenh. is illustrated here and its relationships, status, cultivation and conservation are discussed.